MARRIAGE DISPENSATION IN THE PERSPECTIVE OF QAWAID FIQHIYYAH - Siti Nur Aini (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2025)
The Marriage Act has undergone changes, particularly in regards to the legal marriage age. Prior to the amendments made by this Act, the bride-to-be had to be at least 16 years old and the prospective husband had to be at least 19 years old. then, with the 2019 amendments, the bride judged to be at least 19 years old, as was the bride. The number of underage marriages continues to be considerable despite the higher age requirement. This study combines a literature review. According to the findings of the study, the court's decision to allow for underage marriage has increased the number of cases of underage marriage in. Marriage is an external manifestation of two people's desire to create a happy family (Sakinah, warahmah and mawaddah). The Marriage and Compilation of Islamic Laws Law No. 1 of 1974 outlines marriage as a legal occurrence and outlines the requirements for marriage.for which the bride and husband are responsible. The goal of this study is to understand and analyze the justifications for the petitioner's request for a dispensation as seen through the lenses of state law, customary law, and Islamic law as well as to understand and analyze and determine how the law will be applied to the petitioner's dispensation application